My mini book of fruits (Say Publishing Karachi, 2011)
This vibrant mini book introduces young readers to a colorful world of fruits. With simple text and engaging illustrations, children will learn the names of various fruits, their colors, and their shapes. From juicy apples to sweet berries, this book sparks curiosity and encourages healthy eating habits. Perfect for preschoolers and early elementary students, this mini book is a delightful way to explore the wonderful world of fruits.